Comparison of manual and automatic barcode detection in rough horticultural production systems - Eyahanyo, Felix; Rath, Thomas (International Journal of Agricultural and Biological Engineering, 2019)
Automation of production in the nurseries of flower producing companies using barcode scanners have been attempted but with little success. Stationary laser barcode scanners which have been used for automation have failed due to the close proximity between the barcode and the scanner, and factors such as speed, angle of inclination of the barcode, damage to the barcode and dirt on the barcode. Furthermore, laser barcode scanners are still being used manually in the nurseries making work laborious and time consuming, thereby leading to reduced productivity. Therefore, an automated image-based barcode detection system to help solve the aforementioned problems was proposed. Experiments were conducted under different situations with clean and artificially soiled Code 128 barcodes in both the laboratory and under real production conditions in a flower producing company. The images were analyzed with a specific algorithm developed with the software tool Halcon. Overall the results from the company showed that the image-based system has a future prospect for automation in the nursery.Keywords: automation, barcode detection, horticultural production systems, image processing, barcode scannersDOI: 10.25165/j.ijabe.20191206.4762Citation: Eyahanyo F, Rath T. Comparison of manual and automatic barcode detection in rough horticultural production systems. Int J Agric & Biol Eng, 2019; 12(6): 169–176.